INTERFAITH MARRIAGE IN ISLAMIC FAMILY LAW (Addressing the Doctrinal Provisions and Socio Religious Context in Indonesia) - Muhtadli, Rudi Hartono (Faculty of Law Universitas Muhammadiyah Metro, 2026)
Interfaith marriage has become an important issue in the discourse of Islamic family law, especially in Indonesia, which has religious and cultural diversity. Although the state recognizes freedom of religion, the existing legal provisions often create tensions between national law and religious law, particularly concerning marriages between Muslims and non-Muslims. Law No. 1 of 1974 concerning Marriage limits interfaith marriages, which can only take place with the approval of the relevant authorities. This study employs a qualitative descriptive approach with literature analysis to understand the doctrinal views on interfaith marriage and its implications in Indonesia's socio-religious context. This paper explores the differing views of Islamic jurisprudence on interfaith marriage, such as the strict prohibition in the Shafi'i school, the more flexible stance of the Hanafi school, and the contextual approach of the Maliki school. The study also analyzes public acceptance of interfaith marriages in Indonesia, influenced by social norms, culture, and religious education. In more pluralistic areas, there is greater acceptance of interfaith marriages, while in more conservative regions, such unions are considered taboo. In conclusion, the implementation of Islamic family law concerning interfaith marriage in Indonesia requires a more inclusive and adaptive approach to social development and pluralism, while maintaining a balance between religious freedom and the values upheld by society.